A naturalização da psicologia na saúde: uma arqueogenealogia das práticas psicológicas na saúde pública brasileira - Siebra, Adolfo Jesiel (2018)
This dissertation discusses archaeogenealogically, from the historical-philosophical perspective of knowledge and practices as pointed out by Michel Foucault, the relation between psychological practices and health practices in the Brazilian context. If, in our present days, there is a certain discursiveness within the psychological field with such ambiguous status, being conceived, at the same time, as a psychological and health practice, we consider that, less than a theoretical refinement, this process is taxed by mechanisms of power in full exercise that repeat, incite, approximate statements, making them, if not inseparable, at least an inevitable or unavoidable result of supposed scientific progress. Thus, the scope of this study consists of examining what conditions (discursive and non-discursive) made possible the irruption of this new arrangement in the psychological practices, allowing them to also operate as health practices. In order to do so, some booklets produced by the Center of Technical References in Psychology and Public Policy (CREPOP) were selected, since in these "monuments" are listed some psychological practices which also came to be conceived as health practices. Then, from these documents, we operate a description of the regularities that constitute these discursive practices, verifying in the end that they gravitate, roughly, around two central axes: the legal dimension and the conceptual dimension. In the face of this picture, we subsequently made an incursion into the history of psychology in the Brazilian scenario, in order to analyze how these elements became part of the psi field, and especially, to enter the order of truth. Based on the above, we note that becoming a health practice has not, in many ways, demarcated an abysmal rupture to psi practices. On the contrary, what was established was much more, an update in its modus operandi, because even with the change of scenery, its performance still continued being ruled by certain subservience to certain precepts outside the field, while its function also remained , fundamentally, to operationalize them. Therefore, we consider that perhaps the disastrous past of psychology in Brazil is not so past as we are told, that it may now be present in other forms and modalities. Finally, we do not intend with this work to announce that the task of (re) thinking psychology would have failed, nor to endorse that such a mission would have already been completed. We simply try to demonstrate to those who are willing to make such an undertaking that it is still in progress and that it is up to us, inhabitants of the present, to problematize it.